The role of the resorption phase of remodeling process of bone in development of nonunion after osteosynthesis of the femoral neck medial fracture (review) - Pirogov, Evgeny; Tyazhelov, Olexiy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
We presented an analytical review of scientific information on the mechanisms of local bone resorption within a remodeling process of bone fragments in cases of medial femoral neck fractures. Marginal resorbtion of fragments should be considered during osteosynthesis as a result of this process because result of this process is partial loss of bone material in fracture area, reducing of the geometric parameters of bone fragments, changing of structural and mechanical properties of bone tissue in the vicinity of the zone of fracture and, consequently, violations of tension-deformed state of materials on the verge of «lock – bone» reached in the process of surgery. Most researchers recognize that certain fragments resorption always occurs mostly after fractures of epimetaphiseal bone areas. However there were not described any its possible mechanisms and chronological relationship with stages of reparative regeneration, and an idea of marginal resorption in the initial phase of consolidation of bone fragments is rather vague. In most mechanical or mathematical model process of marginal resorbtion is not taken into consideration which inevitably leads to errors in biomechanical grounding of application of different fixateurs. The authors highlighted information on local and systemic factors that affect the extent and dynamics of local bone resorption and its role in the development of early complications after osteosynthesis of medial femoral neck unstable fractures. We described some typical processes of bone tissue loosing and their relationship to the level of blood circulation. Recognizing the marginal resorption as a typical process of remodeling bone fragments and further study of its mechanisms will help to resolve a problem of treatment of medial femoral neck fractures and to create some novel biomechanically substantiated fixateurs.